Analysis and Optimization of a Small-Scale Oceanic Wave Energy Converter - Mohd Azwir Azlan; Muhammad Hafzal bin Abdul Gani (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Recently, there has been a rise in awareness of ocean wave energy as a potential source of useful energy. Basically, a wave energy converter is a device that converts mechanical energy from ocean waves into electrical energy. This research is about to analyses and optimize the previous small-scale oceanic Wave Energy Converter (WEC) project that is planned to run the generator at 600 rpm and generate about 12kW of electrical power per day. This research were based on analysis and safety considerations in WEC design, such as gear failure analysis, shaft analysis, bearing analysis, buoyancy force, and component optimization. Static analysis is performed on components such as connectors, buoys, and platforms. The results of static analysis of key components, such as gears, shaft bearings, buoy connectors, and platforms, surpass the safety factors that meet the requirements. Shape optimization is also done to reduce the weight of the machine to increase efficiency and ensure that the new design of components is in accordance with the standards. The total weight of the Small-Scale Ocean Wave Energy Converter was successfully reduced by 39.53 %, from 1068.10 kg to 645.83 kg.